UNDERGRADUTE STUDENTS’ ERROR IN USING MORPHOLOGY IN WRITING RECOUNT TEXT - Yulia Agustina; M. Adib Nazri (Universitas Sarjanawiyata Tamansiswa, 2022)
Morphological errors occur when students made morphological aspect of grammar misinformed. The aims of the research to describe the morphological errors and to know the factors that affect students in their writing skill. This research employed descriptive qualitative method. The data was taken from 25 students asked the undergraduate students of the first semester of English Department Hamzanwadi University in making recount text based on their holiday experience and interviewed students to know their difficulties in it. In analyzing the data, the researchers used: identification error, classification error, and explanation error. The findings showed that the most students who made errors in inflectional morpheme consisting 18 (72%) students. It happened because they don’t realize in describing event happening in the past, the text should be in past tense. The second, 13 (52%) students did errors in free morpheme, it occurred because the first language structure is not like the target language, so students forgot to apply the auxiliaries in past form. Next, 6 (24%) students who made errors in compounding because teacher’s style in teaching English. The last, derivational errors made by 5 (20%) students. Based on interview result, they got difficulties in comprehending the structure target language its self and lectures’ teaching style was aspect why students still confuse in comprehending the materials. Hence, to solve these problems te students have to build writing habit in order they familiar with the morphological aspects then flow into the their writing.